On Harmonizing the External Economic Policy among the Countries of the Common Economic Space: Problems and Prospects - Ratushnyak, E. S. (Vestnik MGIMO-Universiteta, 2014)
The article provides the tax systems of the countries of the customs union of Belarus, Kazakhstan and Russia, reveals the differences and identifies the need for harmonization and convergence of the structures and principles of taxation, the general tax reforms and harmonization of fiscal policies of member countries in order to increase the investment attractiveness and competitiveness of the national economies in the process of development and integration. The comparison of the existing tax systems of the three countries revealed differences affecting the implementation and development of the foreign economic activity of companies in terms of the common market, in particular, the main obstacles to doing business are high tax rates as well as different rates of value added tax (further - VAT) regarding indirect taxation, because this tax is the major budget revenue generating tax involved in the pricing and resulted in decreasing in the export potential of the country. One of the major exporters' obstacles of CU, revealed in the paper, is a VAT refund in export transactions, preventing the development of export activity, which reduces the competitiveness of CU on the foreign markets. The harmonization success of fiscal policy depends on the government, and the institution body taking the harmonization, - this paper looks at the necessity of such harmonization among the three countries of customs union, which at present has interstate form while supranational regulation of Eurasian Economic Commission is absent, since it does not have such empowerment. The paper finds the main tax policy directions of harmonization of customs union countries focused on eliminating of the barriers and for easy the implementation of a process for foreign trade enterprises, the development of the participating countries investment attractiveness, the enhancing the products competitiveness, the development of the export activities efficiency on the whole for the formation of the common customs area. In addition, the practicality of the tax ratio and customs legislation is revealed in this paper. It is important in order to fuel the growth of the integration economic performances and equal competitive conditions for participating countries to give consideration to the harmonization of the taxation of the three countries as one of the main directions of development of integration within the framework of the common economic space (further - CES).